Favorable response to immunosuppressive combination therapy with mizoribine and azathioprine in children with primary sclerosing cholangitis. Issue 4 (16th November 2017) - Tajiri, Hitoshi; Zen, Yoh; Takano, Tomoko; Brooks, Stephen
Abstract : Primary sclerosing cholangitis (PSC), with no curative intervention, can progress to end‐stage liver disease. Mizoribine, a purine antimetabolite, has never been used for the management of PSC. To evaluate the role of mizoribine with azathioprine we undertook a preliminary clinical study in children with PSC. Children with PSC and autoimmune features were simultaneously treated with mizoribine and azathioprine. Ursodeoxycholic acid or mesalazine were not regulated. The primary end‐points of our study included improvement of aspartate aminotransferase, alanine aminotransferase, and γ‐glutamyltransferase. Liver histology, immunostaining studies of the liver, and magnetic resonance cholangiopancreatography (MRCP) were also assessed. We have treated four PSC children: two treatment‐naïve patients (cases 1 and 2), and two with established liver cirrhosis (cases 3 and 4). Both case 1 and 2 showed a normalization of liver enzymes and case 2 showed an improvement in MRCP findings. Cases 3 and 4 also showed an improvement in varices, MRCP findings, and liver histology. The combination therapy may be effective for some children with PSC and autoimmune features. By ameliorating both parenchymal inflammation and cholangiopathy of PSC, the therapy might improve the prognosis for patients. It awaits further prospective studies to confirm the efficacy of this therapy in patients with PSC.